On the impact of intra-system interference for ranging and positioning with Bluetooth low energy - Figueiredo e Silva, Pedro; Basiri, Anahid; Lohan, Elena Simona; Pinchin, James; Hill, Chris; Moore, Terry (2015)
This paper focuses on the study of intra-system interference for ranging and positioning applications using Bluetooth Low Energy (BLE). While BLE tries to avoid interference with other protocols in the same frequency band, such as Wi-Fi, the intra-system interference is unavoidable, either due to multipath or simultaneous transmissions in the same channel. This study shows that intra-system interference contributes with a deviation of approximately 5 dBm in the Received Signal Strength (RSS) and by taking this into account the ranging and positioning accuracy can be significantly improved. The study uses data collected from two different environments.